Big data analytics a social network approach - Panda, Mrutyunjaya; Abraham, Ajith; Hassanien, Aboul Ella (CRC Press, Taylor & Francis Group, 2019)
Social networking has increased drastically in recent years, resulting in an increased amount of data being created daily. The book spans numerous disciplines like neural networking, deep learning, artificial intelligence, visualization, e-learning in higher education, e-healthcare, security and intrusion detection.